Urban-Rural Differences in Cardiac Arrest Outcomes: A Retrospective Population-Based Cohort Study - Michael S. Connolly, BSc; Judah P. Goldstein, PCP, PhD; Margaret Currie; Alix J.E. Carter, MPH, MD; Steve P. Doucette, MSc; Karen Giddens, RDMS, RDCS; Katherine S. Allan, PhD; Andrew H. Travers, MSc, MD; Beau Ahrens, MSc; Daniel Rainham, PhD; John L. Sapp, MD (CJC Open, 2022)
Background: Approximately 10% of people who suffer an out-of-hospital cardiac arrest (OHCA) treated by paramedics survive to hospital discharge. Survival differs by up to 19.2% between urban centres and rural areas. Our goal was to investigate the differences in OHCA survival between urban centres and rural areas. Methods: This was a retrospective cohort study of OHCA patients treated by Nova Scotia Emergency Medical Services (EMS) in 2017. Cases of traumatic, expected, and noncardiac OHCA were excluded. Data were collected from the Emergency Health Service electronic patient care record system and the discharge abstract database. Geographic information system analysis classified cases as being in urban centres (population > 1000 people) or rural areas, using 2016 Canadian Census boundaries. The primary outcome was survival to hospital discharge. Multivariable logistic regression covariates were age, sex, bystander resuscitation, whether the arrest was witnessed, public location, and preceding symptoms. Results: A total of 510 OHCAs treated by Nova Scotia Emergency Medical Services were included for analysis. A total of 12% (n = 62) survived to discharge. Patients with OHCAs in urban centres were 107% more likely to survive than those with OHCAs in rural areas (adjusted odds ratio = 2.1; 95% confidence interval = 1.1 to 3.8; P = 0.028). OHCAs in urban centres had a significantly shorter mean time to defibrillation of shockable rhythm (11.2 minutes ± 6.2) vs those in rural areas (17.5 minutes ± 17.3). Conclusions: Nova Scotia has an urban vs rural disparity in OHCA care that is also seen in densely populated OHCA centres. Survival is improved in urban centres. Further improvements in overall survival, especially in rural areas, may arise from community engagement in OHCA recognition and optimized healthcare delivery. Résumé: Contexte: Environ 10 % des personnes qui subissent un arrêt cardiaque en milieu extrahospitalier (ACEH), traité par des intervenants paramédicaux, survivent jusqu’à leur congé de l’hôpital. Le taux de survie peut différer de 19,2 % entre les centres urbains et les régions rurales. Notre étude visait à étudier les différences en matière de survie après un ACEH entre les centres urbains et les régions rurales. Méthodologie: Il s’agissait d’une étude de cohorte rétrospective portant sur des patients ayant subi un ACEH traité par les services médicaux d’urgence de la Nouvelle-Écosse en 2017. Les cas d’ACEH traumatique, prévu et non cardiaque ont été exclus. Les données ont été recueillies à partir du système de dossiers électroniques de soins aux patients des services médicaux d’urgence et de la Base de données sur les congés des patients. L’analyse du système d’information géographique a classé les cas selon qu’ils sont survenus dans un centre urbain (population de plus de 1 000 personnes) ou dans une région rurale, en utilisant les limites du recensement canadien de 2016. Le principal paramètre d’évaluation était la survie à la sortie de l’hôpital. Les covariables utilisées dans la régression logistique multivariée étaient l’âge, le sexe, la réanimation effectuée par des témoins si présents lors de l’arrêt cardiaque, l’emplacement public et les symptômes précédents. Résultats: Au total, 510 ACEH traités par les services médicaux d’urgence de la Nouvelle-Écosse ont été inclus aux fins de l’analyse. En tout, 12 % (n = 62) des sujets ont survécu jusqu’à leur congé hospitalier. Les patients ayant subi un ACEH dans un centre urbain étaient 107 % plus susceptibles de survivre que ceux ayant subi un ACEH dans une région rurale (rapport de cotes ajusté : 2,1; intervalle de confiance à 95 % : 1,1 – 3,8; p = 0,028). Le temps moyen de délivrance d’un choc lors d’un ACEH avec rythme défibrillable est significativement plus court (11,2 ± 6,2 minutes) dans un centre urbain que dans une région rurale (17,5 ± 17,3 minutes). Conclusions: La Nouvelle-Écosse fait état d’une disparité dans les soins de l’ACEH entre les régions urbaines et les régions rurales, que l’on observe également dans les villes densément peuplées. La survie est plus longue dans les centres urbains. Il est possible de prolonger davantage la survie globale, en particulier dans les régions rurales, en sensibilisant la communauté à l’ACEH et en optimisant la prestation des soins de santé.